A compaixão em O apanhador no campo de centeio, de J. D. Salinger - Buarque, Adriana (2005)
Compassion as redemption of the human being. The aim of this work is to show how Holden Caulfield, the character of The catcher in the rye, returns from his isolation of the world by means of his altruistic love, considering 'the other' more important than himself. From the hypothesis that Holden's grief in maintaining innocence leads him to depression, as compassion leads him to the answer for such conflict, the methodological procedures were based on the inductive method for elaborating theses: historical procedures, such as contextualizing the novel, bibliographical research, text selection, analysis, interpretation, organization and composition of the theoretical approach. Contextualizing J. D. Salinger and his narrative leads to a more accurate comprehension of Holden Caulfield. The anguish of being lonely makes him want to die, something that changes when he realizes, benevolently, that the answer to his question is to seek 'the other'. Then, compassion, the need to love, silences his inner pain